2022
DOI: 10.3390/ma15145049
|View full text |Cite
|
Sign up to set email alerts
|

Processing and Microstructure of As-Cast Ti-45Al-2W-xC Alloys

Tomas Cegan,
Kateryna Kamyshnykova,
Juraj Lapin
et al.

Abstract: The metallurgical preparation and microstructure of as-cast Ti-45Al-2W-xC (in at.%) alloys were investigated. Five alloys with carbon content ranging from 0.38 to 1.96 at.% were prepared by vacuum induction melting (VIM) in graphite crucibles, followed by centrifugal casting into graphite moulds. A master 15W-85Al (at.%) alloy with a relatively low melting point and TiC powder were used to facilitate fast dissolution of W during VIM and to achieve the designed content of C in the as-cast alloys, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
(112 reference statements)
0
1
0
Order By: Relevance
“…However, some authors [1,12,13] have reported that the mechanical properties of the TiAl intermetallic depend mainly on their microstructure. Then, fully lamellar microstructure has high strength and creep resistance, while duplex microstructure is softer but possesses higher room temperature elongation to failure.…”
Section: Introductionmentioning
confidence: 99%
“…However, some authors [1,12,13] have reported that the mechanical properties of the TiAl intermetallic depend mainly on their microstructure. Then, fully lamellar microstructure has high strength and creep resistance, while duplex microstructure is softer but possesses higher room temperature elongation to failure.…”
Section: Introductionmentioning
confidence: 99%